Analisis Yuridis Wanprestasi dalam Perjanjian Kerja serta Perlindungan Hukum bagi Para Pihak: Legal Analysis of Default in Employment Agreements and Legal Protection for the Parties - Devia Octi Pertiwi; Cici Marliani; Deva Nur Fateha (Information Technology and Science (ITScience), 2026)
An employment agreement is the primary foundation of an employment relationship, binding workers and employers to fulfill their rights and obligations. However, in practice, breaches of contract or broken promises often occur on both the part of workers and employers. This study aims to analyze the forms of breaches of contract in employment agreements, their legal consequences, and the legal protections available to the injured parties. The research method used is normative juridical, employing statutory, conceptual, and case approaches. Primary legal materials include the Civil Code, Law Number 13 of 2003 concerning Manpower, and Law Number 2 of 2004 concerning the Settlement of Industrial Relations Disputes. The results of the study indicate that breaches of contract by employers are easier to prove and can be subject to administrative and criminal sanctions.In contrast, breaches by workers require a higher standard of proof and rarely result in termination of employment. Preventive legal protection through the standardization of employment agreements and repressive protection through industrial relations dispute-resolution mechanisms have been comprehensively regulated. However, their implementation still faces obstacles, including lengthy settlement processes and disparities in judicial decisions. Legal gaps were also identified in the protection of digital platform workers who lack written employment agreements. This study recommends issuing implementing regulations to categorize the severity of labor violations and revising the law to accommodate non-standard workers in the digital economy era.